(untitled) (Medicine Today, 2015)
A 52 years old non diabetic, normotensive man with aortoiliac and femoropopliteal occlusive disease, combined aortobifemoral and femoropopliteal bypass with silver coated expanded polytetra fluoroethylene (ePTFE) graft was performed. His operation was uneventful, postoperative recovery was excellent. His recovery was early and sent home on 14th postoperative day without symptoms. Medicine Today 2015 Vol.27(1): 34-35